THE IMPACT OF THE INDONESIAN TAX ADMINISTRATION REFORM ON TAX COMPLIANCE AND TAX REVENUE - Eka, I Wayan Agus (Jurnal Ekonomi dan Pembangunan, 2019)
This study investigated the impact of the Indonesian tax administration reform on tax compliance and tax revenue. I used merged provincial-level data obtained from two main sources: Directorate General of Taxes (DGT) and Indonesia Statistic, and I applied multiple regressions with a fixed-effect model. I find that individual taxpayer compliance was positively affected by the tax administration reform. Tax revenue, however, was negatively affected by the tax administration reform due to DGT?s productivity problem meaning that tax potency variables did not affect tax revenue after the tax administration reform was completed. The findings identify several areas for improvements and suggest several policy implications. First, improving administration in Small Taxpayer Office (STO) especially for individual taxpayers is needed. Second, tax revenue strategy focusing on individual taxpayers is needed to materialize improvement in individual taxpayer compliance into tax revenue. Third, problem in productivity suggests that DGT should improve its input side by improving law enforcement, widening delegated authority, and increasing budget allocation.